2015
DOI: 10.1016/j.otsr.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

An original internal fixation technique by tension band wiring with steel wire in fractures of the coronoid process

Abstract: Fractures of the coronoid process, which is a key element in anterior elbow joint stability, represent 14% of proximal ulnar fractures. Optimal treatment should stabilize all fractures associated with elbow instability. Different techniques have been described: suture repair, screws, plates… We propose a series of 5 patients who were treated with an original, easy, tension band wiring fixation technique using steel wire with easy hardware removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…First, a sufficient fixation force can be obtained compared to the suture technique with a suture anchor or Ethibond in the coronoid process fracture of a relatively large bone fragment, which requires sufficient fixation force. Second, compared to fixation with screws and plates that require open reduction, the technique in this study (arthroscopic reduction) causes less damage to the surrounding soft tissue, and the removal surgery is simple [ 6 ]. Third, special instruments, such as screws, plates, and suture anchors, are not required [ 6 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, a sufficient fixation force can be obtained compared to the suture technique with a suture anchor or Ethibond in the coronoid process fracture of a relatively large bone fragment, which requires sufficient fixation force. Second, compared to fixation with screws and plates that require open reduction, the technique in this study (arthroscopic reduction) causes less damage to the surrounding soft tissue, and the removal surgery is simple [ 6 ]. Third, special instruments, such as screws, plates, and suture anchors, are not required [ 6 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ulnar coronoid process fractures are uncommon, and there is no established gold standard for their surgical treatment. The conventional method of treating ulnar coronoid process fractures is open or arthroscopic reduction and fixation using a suture anchor, 2-0 Ethibond suture, screws, plates, and tension band wiring [ 1 , 2 , 5 , 6 , 7 , 8 ]. There are various surgical techniques for treating such fractures, but no superior technique has been established [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A report by Han et al [ 6 ] of the outcomes of 11 isolated Regan and Morrey type III fractures treated by an anterior approach showed an average of 21 months of follow-up, overall flexion arc was 127.3°, average flexion was 130.9 degree, and average pronation and supination were 73.2 and 75.9 degree, MEPS of 92.3 points; these values were very similar to ours (Table 1 ). Mallard et al, [ 22 ] however, reported the results of 5 patients with coronoid process fractures treated by tension band wiring with a minimum of a 1.1-year follow-up. The mean flexion–extension arc of elbow motion was 115.0 ± 9.62 degree, pronation was 86.0 ± 1.87 degree, supination was 85.0 ± 4.47 degree, and MEPS was 81.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, a recent study indicates that ulna coronoid fractures can be treated by internal fixation with frame shape plate and open reduction through anterior approach of the elbow, as it is an effective treatment option with minimal damage and strong fixation [ 12 ]. It has been previously reported that ulna coronoid fractures treated with internal fixation had better mechanical resistance than suture anchors for fixing small fragments and internal fixation with tension band wiring with steel wire is an excellent approach to treat coronoid fractures [ 13 15 ]. Internal fixation with mini plate is effective for early functional exercise as it provides sufficient stability and improves functional outcome [ 16 ].…”
Section: Introductionmentioning
confidence: 99%